PENGGUNAAN TEPUNG TALAS BOGOR (Colocasia esculenta L. Schott) TERHADAP SIFAT FISIK DAN AKSEPTABILITAS NAGGET AYAM PETELUR AFKIR - Obin Rachmawan; Ahmad Taofik; Nono Suwarno (JURNAL ISTEK, 2013)
The Objective of the research was to find out the concentration level of taro flour on chiken nugget culled layer with physical condition (water holding capacity, cooking loss and tenderness) same as treatment control and most preferable acceptability (taste, flavor, tenderness and acceptance). The experimental study was based on Completely Randomized Design, with for treatments (10% tapioca as control, and 10%, 15%, and 20% taro flour usage dosage) with five replication for each treatment. ANAVA test and Tukey test were held to find out the differences of each treatment effect in this reaearch. The result of research showed that taro flour can used in chiken nugget culled layer with concentration 15%.